Pengembangan Sistem Informasi Kredit Poin Mahasiswa Di Fakultas Teknik Universitas Nurul Jadid - Syafiih, M .; Yusman, Beny; Nadiyah, Nadiyah (Journal of Advanced Research in Informatics, 2025)
The management of student credit points at the Faculty of Engineering, Nurul Jadid University (UNUJA) previously used a Laravel 5-based information system that had various limitations. Several important features could not function optimally due to outdated technology, and had not been integrated with the Nurul Jadid University Single Sign-On (SSO) system, thus complicating the centralized authentication process. This study aims to develop a modern, responsive, and integrated student credit point information system with Nurul Jadid University SSO using the Laravel 11 framework. The development method applied is Rapid Application Development (RAD), which focuses on accelerating the development process through prototyping, rapid iteration, and continuous receipt of user feedback. The results showed that the new system was able to fix all previously non-functional features and provide optimal authentication integration with SSO. Testing using the black-box method on all test scenarios resulted in a 100% feasibility rate, proving that the system has functioned according to specifications and met user needs. In addition, external testing showed the highest percentage of 98% (Strongly Agree) and the lowest percentage of 86% (Strongly Agree). These findings are significant because they demonstrate that utilizing the Laravel 11 framework with SSO integration can improve efficiency, accuracy, and transparency in student credit point management, while simultaneously supporting a more structured academic process.